Interdisciplinary Approach for Management of Iatrogenic Internal Root Resorption: A Case Report - Ramazani, Mohsen; Asgary, Saeed; Zarenejad, Nafiseh; Mehrani, Javad (Iranian Endodontic Journal, 2016)
For management of a symptomatic maxillary lateral incisor with dull pain on chewing, suppurative sinus tract, defective metal-ceramic crown and iatrogenic internal root resorption, an interdisciplinary approach was taken. Two-visit nonsurgical treatment with calcium-enriched mixture (CEM) cement, replacement of metal-ceramic crown with all-ceramic crown and corrective periodontal plastic surgery were included in the treatment plan. Six-month and one-year follow-ups revealed complete resolution of signs and symptoms and radiographic healing. This case report highlights the importance of adequate cooling during crown preparation to preserve the pulp vitality and prevent internal resorptive lesions and also the profound sealing ability and biocompatibility of CEM cement. Keywords: Calcium-Enriched Mixture; Interdisciplinary Treatment; Internal Root Resorption